Mixed-Sex Peer Interactions and Adjustment in Chinese Adolescents. - Chen, Xinyin; Hei, Long; Li, Dan; Liu, Junsheng; Yang, Panpan; French, Doran (Applied Research in Quality of Life, 2026)
This longitudinal study examined relations between mixed-sex peer interactions and adjustment in Chinese adolescents. Participants included 461 sixth grade students (223 boys; initial mean age = 12 years) in junior high schools in urban China. Data on mixed-sex peer interactions and social and school adjustment were obtained from multiple sources. The results showed that mixed-sex peer interactions significantly predicted higher social competence one year later. Mixed-sex interactions were associated with reduced loneliness for adolescents who were low on same-sex social preference and increased social competence for those who were high on same-sex social preference. Mixed-sex interactions were also associated with higher social competence and less learning problems for adolescents who were high on opposite-sex social preference. The results indicate the developmental significance of adolescents' mixed-sex peer interactions in the contemporary Chinese context and help alleviate parents' and teachers' concerns about their adverse impact on social and academic development.